Nantucket penny - Axelrod, Steven (A Henry Kennis Nantucket Mystery, 2021)
"The old Nantucket tradition of throwing a penny off the ferry to ensure your eventual return resonates for locals and visitors alike. But that ritual takes a sinister turn when, one by one, people start to disappear and the telltale pennies are found at the scene of the kidnappings. Someone is trying to send a frightening message. The race is on to save the missing people and in order to stop this chilling crime wave, Chief Henry Kennis will have to delve into their personal histories and the scandals of the past. The 6th book in Steven Axelrod's acclaimed series, Nantucket Penny explores forgotten scandals and trauma that generate a ruthless revenge spree"--